Picking Grapefruit, Trinidad, B.W.I. - 25573 - (:unkn) unknown (My University, 2010)
A man picking grapefruit on an estate in Trinidad.
Colour: Orange, green and blue hues; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Citrus--Trinidad and Tobago; Trees--Trinidad and Tobago; Plantations--Trinidad and Tobago; Citrus fruit industry--Trinidad and Tobago; Grapefruit--Trinidad and Tobago; Working class men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Pouches (Containers)--Trinidad and Tobago; Bags; Grapefruit industry--Trinidad and Tobago; [1941]; Harvesting--Trinidad and Tobago